Gap year option for varsity students - Daily Express, (KK) (Daily Express (kk), 2017)
KUALA LUMPUR: The Higher Education Ministry will implement the Gap Year 2017 programme starting September to allow undergraduates to take a year off from studying to pursue their interests. Higher Education Minister Datuk Seri Idris Jusoh said the practice, which was common abroad, would affect eight universities.